Initial Transmission Influence on Saturable Absorber Absorption Activity of Passive Q-Switching Erbium -Doped Fiber Laser System - Ali, Zainab; Abdulsada, Zainab; Arasavalli, Nagamalli; Kadhim, Sally; Akram , Haneen (University of Thi-Qar Journal of Science, 2023)
The initial transmission effect on the activity of Cr+4: YAG saturable absorber with Er +3 doped fiber laser was investigated. Software computer program was built in this study for solving the rate equations model by Rung - Kutta –Fehlberg numerical method. The study reported that the absorption activity of ground state of saturable absorber decreases with the decreasing of the initial transmission, while the activity absorption of excited state begins to increase. Moreover,  the total absorption activity of saturable absorber also decreases with the decreasing of the initial transmission.